2010
DOI: 10.1115/1.4000744
|View full text |Cite
|
Sign up to set email alerts
|

Buoyancy Driven Heat Transfer of Nanofluids in a Tilted Enclosure

Abstract: Buoyancy driven heat transfer of water-based nanofluids in a differentially heated, tilted enclosure is investigated in this study. The governing equations (obtained with the Boussinesq approximation) are solved using the polynomial differential quadrature method for an inclination angle ranging from 0 deg to 90 deg, two different ratios of the nanolayer thickness to the original particle radius (0.02 and 0.1), a solid volume fraction ranging from 0% to 20%, and a Rayleigh number varying from 10 4 to 10 6 . Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
74
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(89 citation statements)
references
References 49 publications
15
74
0
Order By: Relevance
“…It was found that the presence of nanoparticles reduces the strength of flow field, enhances the heat transfer depending on both the strength of convection and the volume fraction of the nanofluid and contributes to stabilize the system. Another study related to natural convection of water-based nanofluids in a differentially heated tilted enclosure was numerically conducted by Kahveci (2010). It was concluded from the results that suspended nanoparticles substantially increase the heat transfer rate and the variation in the average Nusselt number is nearly linear with the solid volume fraction.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the presence of nanoparticles reduces the strength of flow field, enhances the heat transfer depending on both the strength of convection and the volume fraction of the nanofluid and contributes to stabilize the system. Another study related to natural convection of water-based nanofluids in a differentially heated tilted enclosure was numerically conducted by Kahveci (2010). It was concluded from the results that suspended nanoparticles substantially increase the heat transfer rate and the variation in the average Nusselt number is nearly linear with the solid volume fraction.…”
Section: Introductionmentioning
confidence: 99%
“…The effective density of the nanofluid is assumed to be constant and is given by (Kahveci, 2010) as:…”
Section: Problem Statementmentioning
confidence: 99%
“…A review of the literature indicates that numerous industrial geometries were investigated [5][6][7][8][9] but almost works were done using rectangular configurations [10][11][12].…”
Section: Introductionmentioning
confidence: 99%